When Words become too Violent: Silence as a Form of Nonviolent Resistance in the Book of Jeremiah - Hildebrandt, Samuel (Biblical interpretation, 2021)
Throughout the Book of Jeremiah, the prophet is depicted as a victim of verbal and physical violence to which he often responds with fierce imprecations. My study articulates a basic framework in which these troubling passages can be understood and used responsibly by contemporary readers (“Speech as a Response to Violence”) but then argues that Jeremiah’s prayer in Jer 18 violates the balance and boundaries of this framework (“Speech as a Response too Violent”). Inasmuch as this discussion reveals the problems and potential dangers of speech, I offer a reading of Jer 15–16, 26, and 28 that highlights the prophet’s silence as an alternative response to violence. This silence, I argue, is not a form of submissive suffering but an act of public critique and strategic disengagement. Jeremiah’s silence speaks powerfully and peacefully in his own violent context and, by extension, may speak so also in ours.